Analisis Penerapan dan Tantangan Service Excellence serta Dampaknya terhadap Kepuasan Masyarakat di Kelurahan Batu, Kabupaten Sidenreng Rappang - Syamsul Bahri; Muliani Samiri; Andi Nilwana (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2026)
This study aims to analyze the implementation of Service Excellence principles in public services at Batu Subdistrict, Sidenreng Rappang Regency, and to identify the inhibiting factors and their impacts on community satisfaction. The research employs a qualitative descriptive approach with data collection techniques including interviews, observation, and documentation. The findings indicate that the implementation of Service Excellence remains partial; while staff friendliness has begun to improve, the principles of speed, accuracy, transparency, and the use of technology have not yet been optimized. The main constraints stem from limited human resource competencies, the absence of a digital-based service system, and inadequate supporting facilities and infrastructure. As a result, community satisfaction has increased but not to an optimal level, as reflected in prolonged service times and inconsistent information. This study recommends strengthening the capacity of public officials through continuous training, accelerating the digital transformation of subdistrict services, and improving standard operating procedures as strategic policy measures to enhance public service quality and community satisfaction.